The interplay between self-evaluation, goal orientation, and self-efficacy on performance and learning - Double, K; Birney, D (Cognitive Science Society, 2017)
Objective Self-awareness Theory (Duval and Wicklund, 1972) proposes that self-evaluation increases an individual’s awareness of any discrepancy between their current performance and an internal goal. In the current study we prompted self-evaluation throughout an intelligence test (Analysis-Synthesis Test – AST) using confidence ratings (CR). AST performance, the extent to which participants incidentally learnt task-relevant rules (learning rules was unnecessary because they were provided), self-efficacy, and goals, were assessed. The results indicated an effect of performing CR on both performance and rule learning, but the effect depended on self-efficacy. Compared to matched controls (n=45), participants who performed CR (n=41) and had high self-efficacy performed better on the AST but learnt fewer rules. Performing CR had no effect on participants low in self-efficacy. This suggests that selfevaluation interacts with self-efficacy to modify participants’ goals, specifically CR appear to shift individuals high in self-efficacy from a mastery goal to a performance goal